The perception of the academicians on characteristics of shari'ah committee (SC) for Islamic banks in Malaysia - Saleh , Haider Mahdi (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
Islamic banks (IBs) should comply with Shari'ah to gain the confidence of the Muslim society in particular and the world at large. Islamic banks necessitate credible and independent bodies which ensure that all of their actions and transactions are compliant with Shari'ah principles. This raises the question of the characteristics of Shari'ah committee (SC) members in Islamic banks. This is because there are many factors that influence for the SC members in Islamic banks. The researcher applied this research in Malaysia because it is one of the advanced countries in the field of Islamic banks, and the prospects for Malaysia becoming a leader in this field. Therefore, this study is designed to examine the perception of SC related academicians in three faculties (Economic, Law, and Shari'ah) in Malaysia on the characteristics of SC in IBs. The study selected five variables that influence SC works in Islamic banks, which are attributes of SC members, duties and responsibilities, independence, professional advice, and performance. The study utilises questionnaires to obtain the perception of SC related academicians. There are 96 academicians who are actively involved as the respondents of the study. The study renders the importance of SC's characteristics in order to verify the Islamic activities and transactions. Additionally, it prompts the SC to establish a special Shari'ah review report for the directors, regulators, and management. Furthermore, the respondents perceived that SC should have responsibility to shareholder at first level than depositors, and customers. The respondents also support that SC should also legally responsible to customers.